Comprehensive understanding of DOM reactivity in anaerobic fermentation of persulfate-pretreated sewage sludge via FT-ICR mass spectrometry and reactomics analysis. (1st February 2023) - Liu, Jibao; Wang, Chenlu; Hao, Zhineng; Kondo, Gen; Fujii, Manabu; Fu, Qing-Long; Wei, Yuansong
Highlights: A novel strategy to explore DOM transformation by FT-ICR MS and data mining. DOM transformation patterns provide potential fingerprint tracking performance. Keystone molecules in DOM network presented as potential indicator or regulators. Abstract: Understanding the composition and reactivity of dissolved organic matter (DOM) at molecular level is vital for deciphering potential regulators or indicators relating to anaerobic process performance, though it was hardly achieved by traditional analyses. Here, the DOM composition, molecular reactivity and transformation in the enhanced sludge fermentation process were comprehensively elucidated using high-resolution mass spectrometry measurement, and data mining with machine learning and paired mass distance (PMD)-based reactomics. In the fermentation process for dewatered sludge, persulfate (PDS) pretreatment presented its highest performance in improving volatile fatty acids (VFAs) production with the increase from 2, 711 mg/L to 3, 869 mg/L, whereas its activation in the presence of Fe (as well as the hybrid of Fe and activated carbon) led to the decreased VFAs production performance. In addition to the conventional view of improved decomposition and solubilization of N-containing structures from sludge under the sole PDS pretreatment, the improved VFAs production was associated with the alternation of DOM molecular compositions such as humification generating molecules with high O/C, N/C, S/C and aromatic index (AImod ). Machine learning was capable of predicting the DOM reactivity classes with 74–76 % accuracy and found that these molecular parameters in addition to nominal oxidation state of carbon (NOSC) were among the most important variables determining the generation or disappearance of bio-resistant molecules in the PDS pretreatment. The constructed PMD-based network suggested that highly connected molecular network with long path length and high diameter was in favor of VFAs production. Especially, -NH related transformation was found to be active under the enhanced fermentation process. Moreover, network topology analysis revealed that CHONS compounds (e.g., C13 H27 O8 N1 S1 ) can be the keystone molecules, suggesting that the presence of sulfur related molecules (e.g., cysteine-like compounds) should be paid more attention as potential regulators or indicators for controlling sludge fermentation performance. This study also proposed the non-targeted DOM molecular analysis and downstream data mining for extending our understanding of DOM transformation at molecular level. Graphical abstract: Image, graphical abstract